Tìm x X²-9=3(x-3) 3(3x²-1)=6-2(3x+2) Giúp em với ạ

Tìm x
X²-9=3(x-3)
3(3x²-1)=6-2(3x+2)
Giúp em với ạ

2 bình luận về “Tìm x X²-9=3(x-3) 3(3x²-1)=6-2(3x+2) Giúp em với ạ”

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
        x²-9=3(x-3)
    ⇒(x-3)(x+3)-3(x-3)=0
    ⇒(x-3)(x+3-3)=0
    ⇒x-3=0          ⇒x=3
       x+3-3=0        x=0
    Vậy x∈(0;3)

    Trả lời
  2. #wdr
    x^2-9=3(x-3)
    x^2-9=3x-9
    x^2-3x=-9+9
    x(x-3)=0
    => x=0
    => x-3=0
    x=3
    Vậy x={0;3}
    —–
    3(3x^2-1)=6-2(3x+2)
    9x^2 -3=6-6x-4
    9x^2 +6x=-4+3
    9x^2+6x=-1
    9x^2+6x+1=0
    (3x+1)^2=0
    3x+1=0
    3x=-1
    x=-1/3
     

    Trả lời

Viết một bình luận

Câu hỏi mới